2017
DOI: 10.1136/eb-2017-102820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drinking on late-life brain and cognition

Abstract: Alcohol consumption is common in Western countries and has been increasing in older adults. Latest figures from Great Britain suggest 75% of those over 65 years drink, an increase from 71% 10 years ago. Chronic heavy intake is a well-established cause of brain atrophy and dementia, with a recent long-term prospective study from the USA reporting a doubling of the odds of later severe memory impairment in those with a history of an alcohol use disorder. Drinking of moderate amounts has been reported to be prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 49 publications
(39 reference statements)
3
64
0
1
Order By: Relevance
“…However, there are additional outcomes, such as dementia and psoriasis, for which accumulating evidence suggests that alcohol use might be a risk factor. 31 , 32 , 33 In combination, these limitations suggest that our results are likely to underestimate both the health risks and overall attributable burden of alcohol use.…”
Section: Discussionmentioning
confidence: 89%
“…However, there are additional outcomes, such as dementia and psoriasis, for which accumulating evidence suggests that alcohol use might be a risk factor. 31 , 32 , 33 In combination, these limitations suggest that our results are likely to underestimate both the health risks and overall attributable burden of alcohol use.…”
Section: Discussionmentioning
confidence: 89%
“…Prolonged use of inhaled or ingested street cannabis in patients with MS has been associated with poor performance on cognitive domains commonly affected in this population [33]. In a neuropsychological and f-MRI study [34] cannabis use was associated with compromised cerebral compensatory mechanisms, already faulty in MS. Lastly, regarding alcohol consumption, chronic heavy intake is a well-established cause of brain atrophy and dementia [35] although this association has not been specifically explored in MS.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between drinking and cognitive performances in old age remains a highly controversial issue. The deleterious effect of heavy wine consumption on cognitive evolution over time in elderly controls has been already documented [ 8 , 9 , 10 , 64 , 65 ]. Several lines of evidence have suggested that moderate drinking could have a slight positive impact on memory and verbal abilities [ 66 , 67 ] but negative data have been also reported [ 64 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…A U-shape relationship between cognitive performance and wine consumption has been postulated with a marked detrimental effect of heavy drinking but a decrease of Alzheimer disease (AD) and dementia risk among light to moderate drinkers. However, this latter association has been challenged due to confounding by socioeconomic class and intelligence (for review see References [ 8 , 9 , 10 ]).…”
Section: Introductionmentioning
confidence: 99%